Investigations of conducting polymers, carbon materials, oxide and sulfide materials for supercapacitor applications: a review - Dhilip Kumar, R.; Nagarani, S.; Sethuraman, V.; Andra, Swetha; Dhinakaran, V. (Chemical papers, 2022)
Supercapacitors are gaining popularity as energy storage devices because of their quick charge/discharge rates, prolonged cycle stability, and high specific power. Low-cost active electrode materials have piqued the interest of researchers in energy storage applications, notably supercapacitor applications. Carbon-based electrode materials have demonstrated excellent performance for electrochemical double-layer capacitors because of outstanding chemical and physical properties, low cost, large expanse, conduction, and extended life at high temperatures. Notably, graphene compound materials performed well for supercapacitors and had a long life of 335 000 cycles. Conducting polymers have exceptional and critical characteristics, such as metal-like conduction and reversible ability between redox states. Recent research interests include the creation of novel materials, namely mixed metal oxides and metal sulfides, for supercapacitors applications. The electrodes of supercapacitors, which are mostly made of metal oxides (Co 3 O 4 , MnO 2 , WO 3 , NiO, and TiO 2 ), have a high degree of stability and retention (up to 94%). Currently, metal sulfide-based materials, including CoNi 2 S 4 and Ni 3 S 2 , have attained specific capacitance values of up to 3296 F/g. When compared to standard capacitors, the supercapacitors outperformed them and employed high power density storage devices. The electrodes of supercapacitors, which are mostly made of metal oxides (Co 3 O 4 , MnO 2 , WO 3 , NiO, and TiO 2 ), have a high degree of stability and retention (up to 94 percent). Presently, the review focuses on active electrode materials for supercapacitors such as carbon-based materials, conducting polymers, metal oxides, and metal sulfide compounds. The objective of this review is fivefold: (1) to present the fabrication of symmetric and asymmetric supercapacitor cells; (2) to describe the performance of carbon-based materials for electrochemical double-layer capacitor; (3) to describe the performance of conducting polymers for supercapacitors in the aqueous and non-aqueous electrolyte; (4) to describe the high-performance metal oxide and metal sulfide for supercapacitor; (5) to outline the major challenges in the technology development and this technology is far more advanced than batteries and has been utilized in a wide range of sectors, including electronics, industries, medicine, and the military.